2016
DOI: 10.1038/srep20366
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear protein GmbZIP110 has transcription activation activity and plays important roles in the response to salinity stress in soybean

Abstract: Plant basic-leucine zipper (bZIP) transcription factors play important roles in many biological processes and are involved in the regulation of salt stress tolerance. Previously, our lab generated digital gene expression profiling (DGEP) data to identify differentially expressed genes in a salt-tolerant genotype of Glycine soja (STGoGS) and a salt-sensitive genotype of Glycine max (SSGoGM). This DGEP data revealed that the expression (log2 ratio) of GmbZIP110 was up-regulated 2.76-fold and 3.38-fold in SSGoGM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 54 publications
4
45
0
Order By: Relevance
“…The soybean gene GmactinII (accession number: NM_001250673, forward primer, 5′‐ATCTTGACTGAGCGTGGTTATTCC‐3′; reverse primer, 5′‐GCTGGTCCTGGCTGTCTCC‐3′) was used as an internal control for the detection of the expression of eight key genes involved in Na + homeostasis in soybean. Similar results were obtained from the relative gene expression data using the change in threshold cycle method as described by Xu et al (). The qRT‐PCR analysis was repeated in three independent experiments.…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…The soybean gene GmactinII (accession number: NM_001250673, forward primer, 5′‐ATCTTGACTGAGCGTGGTTATTCC‐3′; reverse primer, 5′‐GCTGGTCCTGGCTGTCTCC‐3′) was used as an internal control for the detection of the expression of eight key genes involved in Na + homeostasis in soybean. Similar results were obtained from the relative gene expression data using the change in threshold cycle method as described by Xu et al (). The qRT‐PCR analysis was repeated in three independent experiments.…”
Section: Methodssupporting
confidence: 82%
“…cDNA was synthesized from 3.0‐μg total RNA by PrimeScript™ RT Reagent Kit (TaKaRa) using random primers in a 20‐μl reaction system. Quantitative RT‐PCR (qRT‐PCR) was performed on a Roche Light Cycler 2.0 with Light Cycler software (build 4.1.1.21) as described previously (Xu et al, ). Briefly, 1 Îźl of cDNA was added to 5 Îźl of SYBR ÂŽ Premix Ex Taq™ (TaKaRa Bio Inc., Shiga, Japan, http://www.takara-bio.com), together with 0.8 Îźl of each gene‐specific primer (forward and reverse, at 10 mM), and the final volume was brought to 10 Îźl with DNase‐free water.…”
Section: Methodsmentioning
confidence: 99%
“…In soybean, the GmbZIP genes, such as GmbZIP44 , GmbZIP62 , GmbZIP78 , GmbZIP132 , GmbZIP110 and GmbZIP1 , were responsive to multiple stress treatment [15, 16, 33, 41]. In the present study, the results showed that the GmFDL19, which has a high amino acid sequence similar to the Arabidopsis ABF/AREB subfamily members, was determined to be a group A member (Fig 1A).…”
Section: Discussionmentioning
confidence: 51%
“…Furthermore, the transgenic tobacco plants also showed increased seed yields compared to the control plants. Likewise, Xu et al (2016) showed that transgenic Arabidopsis and soybean seedlings overexpressing a soybean bZIP TF designated as GmbZIP110 had improved salt tolerance, suggesting that GmbZIP110 functions as a positive regulator involved in salt stress tolerance. Functional analysis of GmbZIP110 in transgenic Arabidopsis revealed that this gene could bind to the ACGT motif and regulate many downstream target genes (Cao et al, 2017).…”
Section: Functions Of Transcription Factorsmentioning
confidence: 99%